MEMBANGUN LAYANAN IMIGRASI YANG BERINTEGRITAS: ANALISIS LITERATUR TENTANG ETIKA PELAYANAN PUBLIK DAN KEPUASAN MASYARAKAT: BUILDING IMMIGRATION SERVICES WITH INTEGRITY: AN ANALYSIS OF THE LITERATURE ON PUBLIC SERVICE ETHICS AND PUBLIC SATISFACTION - Yahya, Muhammad Ilham; Purnomo, Agung Sulistyo; Maulidia, Hanifa (Journal of Administration and International Development, 2025)
Abstrac Public service ethics plays an important role in improving the quality of immigration services in Indonesia. This study aims to analyze the relationship between the application of service ethics and the level of satisfaction of immigration service applicants. Using a literature study method with a qualitative approach, data was collected from various scientific sources. The results of the analysis show that each of the principles of fairness, transparency, accountability, and empathy contribute significantly to increasing public satisfaction. Although technology based innovations have been implemented, the ethical behaviour of employees remains a key factor in shaping the service experience. The main barriers to ethics implementation include rigid bureaucratic culture and weak public oversight. Therefore, strengthening regulations, ethics based training and community engagement are important strategies in building immigration services with integrity. Keywords: Public Service Ethics, Applicant Satisfaction, Immigration Services, Bureaucratic Reform, Good Governance Abstrak Etika pelayanan publik memegang peranan penting dalam meningkatkan kualitas layanan imigrasi di Indonesia. Penelitian ini bertujuan untuk menganalisis hubungan antara penerapan etika pelayanan dan tingkat kepuasan pemohon layanan imigrasi. Menggunakan metode studi literatur dengan pendekatan kualitatif, data dikumpulkan dari berbagai sumber ilmiah. Hasil analisis menunjukkan bahwa setiap prinsip keadilan, transparansi, akuntabilitas, dan empati berkontribusi signifikan terhadap peningkatan kepuasan masyarakat. Meskipun inovasi berbasis teknologi telah diterapkan, perilaku etis pegawai tetap menjadi faktor kunci dalam membentuk pengalaman layanan. Hambatan utama dalam implementasi etika diantaranya budaya birokrasi yang kaku dan lemahnya pengawasan publik. oleh karena itu, penguatan regulasi, pelatihan berbasis etika, dan pelibatan masyarakat menjadi strategi penting dalam membangun layanan imigrasi yang berintegritas. Kata Kunci: Etika Pelayanan Publik, Kepuasan Pemohon, Layanan Keimigrasian, Reformasi Birokrasi, Good Governance